2014
DOI: 10.1038/ki.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal pneumonia infection is associated with end-stage renal disease in adult hospitalized patients

Abstract: Pneumococcal disease leads to renal complications ranging from persistent proteinuria to end-stage renal disease (ESRD) in pediatric patients. However, long-term renal effects after pneumococcal pneumonia infection in adult patients remains largely unknown. To evaluate this we conducted a population-based retrospective cohort study consisting of 18,733 adult patients at the time of pneumococcal pneumonia diagnosis, using claims data from Taiwan's National Health Insurance Research Database (NHIRD) with a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Frequent exposure to antibiotics is the main driver of ABR 1 . Patients with reduced eGFR have a higher risk of antimicrobial exposure due to their susceptibility to infections 6 , 8 , 9 , 18 20 , either prescribed by physicians or self-prescribed. Infection susceptibility due to immune dysfunction has also been proposed in patients with impaired renal function, including increased production of reactive oxygen species (ROS), accumulation of toxic products, and functional abnormalities of monocytes, T lymphocytes and natural killer cells 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Frequent exposure to antibiotics is the main driver of ABR 1 . Patients with reduced eGFR have a higher risk of antimicrobial exposure due to their susceptibility to infections 6 , 8 , 9 , 18 20 , either prescribed by physicians or self-prescribed. Infection susceptibility due to immune dysfunction has also been proposed in patients with impaired renal function, including increased production of reactive oxygen species (ROS), accumulation of toxic products, and functional abnormalities of monocytes, T lymphocytes and natural killer cells 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported an association between pneumonia and subsequent acute kidney injury and end-stage renal disease, supporting our findings that infections may trigger not only acute but also chronic renal damage. 37,38…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a relationship between chronic renal disease and PP, although the pathophysiological mechanisms involved are not well understood. (25) Several existing studies have suggested that a high risk of pneumococcal disease is associated with primary immunodeficiency due to B cell defects. (26) Solid tumors and hematological malignancies also predispose individuals to infections, especially by gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%